2020
DOI: 10.1177/0956462419896478
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of virologic suppression and improvement in comorbidities after simplification to raltegravir plus boosted darunavir among treatment-experienced HIV-infected patients

Abstract: The use of two potent, well-tolerated, drugs could permit the maintenance of virologic suppression even in heavily pretreated people living with HIV. In this retrospective, multicenter, simplification study (NCT03348449), we included those patients with virologic suppression who switched to raltegravir (RAL) plus boosted darunavir (b/DRV). Overall, 345 patients (75 females, 25%) were included. Patients were largely pretreated (mean, 9.4 regimens), suppressed for a median of 41.1 months. Fifty patients had ≥1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is becoming increasingly clear that, in carefully selected patients, dual therapy is efficacious, with potential to reduce drug toxicity and cost 36 . There is growing evidence to support a switch to dual therapy once viral suppression is maintained on a standard three‐drug regimen 34,37,38 . However, it is important to note that none of the currently available two‐drug regimens has anti‐hepatitis B virus (HBV) activity 39 .…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming increasingly clear that, in carefully selected patients, dual therapy is efficacious, with potential to reduce drug toxicity and cost 36 . There is growing evidence to support a switch to dual therapy once viral suppression is maintained on a standard three‐drug regimen 34,37,38 . However, it is important to note that none of the currently available two‐drug regimens has anti‐hepatitis B virus (HBV) activity 39 .…”
Section: Managementmentioning
confidence: 99%
“…36 There is growing evidence to support a switch to dual therapy once viral suppression is maintained on a standard three-drug regimen. 34,37,38 However, it is important to note that none of the currently available two-drug regimens has anti-hepatitis B virus (HBV) activity. 39 Thus, only select patients, specifically those without HBV coinfection and no evidence of resistance to either agent, have been included in the major trials of two-drug regimens.…”
Section: Two-drug Regimensmentioning
confidence: 99%
“…Dual therapies for maintenance in heavily antiretroviral therapy-experienced people with HIV Drug-sparing regimens (a regimen with less than three antiretrovirals or a decrease in the expected number of drug classes) are most often recommended in maintenance treatment (optimization of an ART composition in case of stable therapeutic success) as shown in Table 3. These recommendations are based on studies conducted most often in HICs and sometimes in heavily ARTexperienced PWH (beyond second-line) with a stable undetectable HIV viral load when enrolled [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. The key goals are clinical: avoid long-term toxicity (cardiometabolic, renal and bone adverse event) [67,77,78], optimize the impact on any newly diagnosed comorbidities, and minimize drug-drug interactions.…”
Section: Drug-sparing Regimens In Second Linementioning
confidence: 99%
“…While therapy has not yet moved to single agents, potent two drug therapies are being explored. In this regard, several studies have shown that a PI can be part of a successful two drug therapy regimen (Casado et al, 2020; Di Cristo et al, 2020; Hawkins et al, 2019; Huang et al, 2019; Vizcarra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%